Testcross performance of Striga-resistant maize inbred lines and testers with varying levels of Striga reaction - Zebire, D.; Menkir, A.; Adetimirin, V.; Mengesha, W.; Silvestro, M.; Gedil, M. (Springer, 2024)
Background: Using a desirable tester is considered one method used to maximise genetic differences among test crosses derived from new inbred lines and improves the overall performance of maize. Thus, this study aimed to evaluate the potency of the tester with varying levels of resistance to *Striga hermonthica* in determining the testcross performance of the hybrids for *Striga* resistance and yield-related traits.